2014
DOI: 10.1371/journal.pone.0088788
|View full text |Cite
|
Sign up to set email alerts
|

Th1 Response and Systemic Treg Deficiency in Inclusion Body Myositis

Abstract: ObjectiveSporadic inclusion body myositis (sIBM), the most frequent myositis in elderly patients, is characterized by the presence muscle inflammation and degeneration. We aimed at characterizing immune responses and regulatory T cells, considered key players in the maintenance of peripheral immune tolerance, in sIBM.MethodsSerum and muscle tissue levels of 25 cytokines and phenotype of circulating immune cells were measured in 22 sIBM patients and compared with 22 healthy subjects. Cytokine data were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 30 publications
3
78
0
Order By: Relevance
“…A more recent report shows a significant decrease in circulating Tregs in IBM patients compared to nonmyositic controls 82. Functionality of the remainder of peripheral Tregs with regard to proliferation‐suppression of autologous T cells, however, was unaffected 82. This study also confirmed the previous finding that Tregs are indeed present in inflamed muscle of IBM patients 82.…”
Section: Pathomechanisms In Ibmsupporting
confidence: 87%
See 4 more Smart Citations
“…A more recent report shows a significant decrease in circulating Tregs in IBM patients compared to nonmyositic controls 82. Functionality of the remainder of peripheral Tregs with regard to proliferation‐suppression of autologous T cells, however, was unaffected 82. This study also confirmed the previous finding that Tregs are indeed present in inflamed muscle of IBM patients 82.…”
Section: Pathomechanisms In Ibmsupporting
confidence: 87%
“…Functionality of the remainder of peripheral Tregs with regard to proliferation‐suppression of autologous T cells, however, was unaffected 82. This study also confirmed the previous finding that Tregs are indeed present in inflamed muscle of IBM patients 82. To which degree this report is specific to IBM or if similar results were to be obtained in other inflammatory myopathies remains to be investigated.…”
Section: Pathomechanisms In Ibmsupporting
confidence: 86%
See 3 more Smart Citations